The Determinants of Household Labor Supply in Georgia, France and Romania: A Comparative Study - George BERULAVA; George CHIKAVA (Eurasian Journal of Business and Economics, 2012)
This paper aims to shed light on the determinants of household labor supply by conducting comparative study and by applying the collective labor supply model. On the basis of data from Generations and Gender Survey (GGS) we tested parametric restrictions imposed by two alternative (unitary and collective) household labor supply models on Georgian, French and Romanian data sets. Our comparison of household labor supply behavior and patterns reveals some similarities, but also several differences across countries. First, the study results suggest that own and partner’s wages, and distribution factors are important determinants of household labor supply in all countries in this study. Second, we found some similarities in the preference structures and in the impact of personal and demographic characteristics on the household behavioral patterns across countries. Third, the study results show that the household labor supply patterns across countries differ substantially. Fourth, we found that collective model is not equally applicable for describing household labor supply in different labor market regimes. For France and Romania, the evidence supports appropriateness of the collective household labor supply model, while in Georgia household labor supply behavior cannot be adequately described by either unitary or collective model.